Hydrogeological conditions in Dun valley of Dang, western Nepal: a case study (Journal of Nepal Geological Society, 1996)
The Dun Dang Valley constitutes a closed groundwater basin in the midst of Himalaya. It is underlain by fluvio-lacustrine sediments which form unconfined to confined aquifer system. The hydrogeological situation in the valley is inferred from drilling data of the Groundwater Resources Development Board (GWRDB), HMG/N. The study reveals existence of a number of groundwater sub-basins each having its own hydraulic system.